Sunday

April 20, 2014

April 20, 2014

Posted by **Sally** on Sunday, April 14, 2013 at 7:57am.

2x^2+7x=0

X(2x+7)=0

X=0 or 2x+7=0. ( the answer in the book was x=-7/2, how?

And. X^2-4=2x-4

Is it x^2-4-2x+4=o ??? If so!' how do I continue?

- Math -
**Reiny**, Sunday, April 14, 2013 at 9:41am2x^2+7x=0

X(2x+7)=0

X=0 or 2x+7=0

ok so far

Now, if the product of two numbers (A)(B) = 0

that can only be true of one of the, or both , are equal to zero.

(try multiplying any two numbers to get a result of 0)

so either x=0 or 2x+7 = 0

x = 0 says it all

in

2x+7 = 0

2x = -7 , (simple equation rule)

x = -7/2 , (simple equation rule)

your second question:

x^2 - 2x = 0 , after you take everything to the left

x(x-2) = 0

same as above and even simpler.

- Math -
**Bosnian**, Sunday, April 14, 2013 at 9:49am2 x ^ 2 + 7 x = 0

x ( 2 x + 7 ) = 0

Obviously solution x = 0

2 x + 7 = 0 Subtract 7 to both sides

2 x + 7 - 7 = 0 - 7

2 x = - 7 Divide both sides by 2

x = - 7 / 2

Solutions x = 0 and x = - 7 / 2

x ^ 2 - 4 = 2 x - 4 Add 4 to both sides

x ^ 2 - 4 + 4 = 2 x - 4 + 4

x ^ 2 = 2 x Subtract 2 x to both sides

x ^ 2 - 2 x = 2 x - 2 x

x ^ 2 - 2 x = 0

x ( x - 2 ) = 0

Obviously solution x = 0

x - 2 = 0 Add 2 to both sides

x - 2 + 2 = 0 + 2

x = 2

Solutions x = 0 and x = 2

**Related Questions**

Math - I have 4 math problems that need to be solved by using factoring. I am ...

math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

Math - Please show the solutions! 1.) x+y-2(2x-3y) 2.) x+y/2 - 3x-y/4 + x-5y/8 3...

math (algebra 2) - ok, I think this is called factoring binomials... how do you ...

maths - if sinA+cosA=1/5, then a value of tanA/2 satisfies which of the equation...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...